International Information Transfer and SDI - Stewart, Alan K.; Williams, Martha E.; Illinois Inst. of Tech., Chicago ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1972)
A summary is presented of data gathered for a survey of information center services in the form of statistics for a hypothetical typical information center. The extent of information transfer on national and international levels among the responding centers is discussed. (Author)
ERIC Note: (0 References).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Information Centers; Information Dissemination; Information Services; Information Utilization; International Programs; Selective Dissemination of Information; Information Transfer